Implementation of web scraping on github task monitoring system - Rolly Maulana Awangga; Syafrial Fachri Pane; Restiyana Dwi Astuti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Evolution of information and technology increasingly sophisticated, also influential in the field of education. One of the implementation of information and technology development in the field of education is e-learning or electronic learning. GitHub social network can be one of the e-learning media in studying software development because GitHub provides access control The number of contributors who commits or change in a repository to make the duration of the calculation process to fill the parameter value that has been determined. Based on the issue, this research aims to build a page capable of integrating information from the GitHub repository page. Integration of information will be made by utilizing web scraping technology. With a web page that integrates information from the GitHub repository page to get repository, collaborators, commits, and issues information, the lecturer does not need to calculate how often the participant contributes to the task.